Pengaruh Ketersediaan Koleksi Terhadap Kebutuhan Informasi Siswa SMP Negeri 6 Payakumbuh - Lusi Ariska; Gustina Erlianti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The objectives of this research are: (1) to describe the availability of collections in the Payakumbuh 6 Public Middle School Library; (2) to describe the information needs of students at SMP Negeri 6 Payakumbuh; (3) to describe the influence of collection availability on the information needs of students at SMP Negeri 6 Payakumbuh.This research is a type of quantitative research with descriptive methods. Data was obtained through distributing questionnaires directly at SMP Negeri 6 Payakumbuh. The population in this study was class IX students, totaling 128 students. The sampling technique used random sampling technique with 56 respondents. In this research, the data analysis technique uses quantitative descriptive statistics. Based on the results of the analysis, the results obtained are, first, the availability of collections in the Library of SMP Negeri 6 Payakumbuh has been categorized as good with an average value of 3.16, second, the information needs of students at SMP Negeri 6 Payakumbuh can be categorized as good with an average value of 3.20, third is the influence of collection availability on the information needs of students at SMP Negeri 6 Payakumbuh, namely the collection availability variable (X) influences the information needs variable (Y), the R value is 0.833 with a value of 69.4%, the remaining 30.6% is influenced by factors -other factors. So it can be said to be good.